The Relationship Between Family Support and the Success of Early Breastfeeding Initiation (Ebi) at Teungku Peukan Regency General Hospital Southwest Aceh - Eka Susanti; Anggia Murni; Cut Nyak Yulia; Elly Febrianty; Dian Kurniawati (Athallah Publishing, 2026)
Early Breastfeeding Initiation (EBI) is one of the important efforts in improving the health of newborns. EBI provides benefits in increasing the success of breastfeeding and strengthening the bond between mother and baby. However, the implementation of EBI is still not optimal. One of the factors that affect the success of EBI is family support, both in emotional, informational, and instrumental forms. To determine the relationship between family support and the success of Early Breastfeeding Initiation (EBI) at Teungku Peukan General Hospital, Southwest Aceh Regency in 2026. This study is an analytical research with a cross-sectional approach. The population in this study is all maternity mothers at Teungku Peukan General Hospital as many as 62 people. The sampling technique used a total sampling with a sample of 62 respondents. Data collection was carried out using questionnaires and observation sheets. Data analysis used the Chi-Square test with a 95% confidence level (α = 0.05). The results showed that most of the respondents received family support, namely 38 people (61.3%) and more than half of the respondents successfully implemented EBI, namely 35 people (56.5%). The results of the statistical test obtained a p-value = 0.004 (p < 0.05) which showed a significant relationship between family support and EBI success. Conclusion: Based on the results of the study, it can be concluded that there is a significant relationship between family support and the success of Early Breastfeeding Initiation (EBI) at Teungku Peukan General Hospital, Southwest Aceh Regency in 2026. It is hoped that health workers can improve education not only to mothers but also to families in order to provide optimal support in the implementation of EBI.